A TECHNIQUE FOR AVOIDING THE EFIE "INTERIOR RESONANCE" PROBLEM APPLIED TO AN MM SOLUTION OF ELECTROMAGNETIC RADIATION FROM BODIES OF REVOLUTION - Steyn, Pierre (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Various surface integral equation formulations, including the electric (EFIE) and magnetic (MFIE) field integral equations, suffer from what is commonly known as the "interior resonance" problem. There are a number of remedies to this problem of which many involve modifying the integral equation formulation and result in increased computational effort and computer storage re- quirements. In an attempt to avoid this the application of a remedy, proposed in the literature, which requires no modification to the formulation has been investigated. This involves the detection of interior resonance frequencies and correction of the current by removing the mode responsible for the 'interior resonance". In the literature, the success of the remedy has been demonstrated for two-dimensional scattering problems involving PEC cylinders. In this work it is demonstrated that, while the correction of the MM (moment method) solution is successful when an "interior resonance" has been detected, the detection of the interior resonance frequencies can be extremely difficult in an MM solution of radiation from composite bodies of revolution. In fact, a foolproof computational algorithm for detecting interior resonance frequencies for this class of problems is yet to be developed. [Vol. 10, No. 3 (1995), Special Issue on Advances in the Application of Method of Moments to Electromagnetic Radiation and Scattering Problems, pp 116-128